PERAN KEBIJAKAN MONETER SYARIAH DALAM MENJAGA STABILITAS HARGA DAN PERTUMBUHAN EKONOMI - Ahmad Wahyudi Zein; Aditya Putra Piliang; Elma Fiisma Dalimunthe; Rafly Ramadhan Simanjuntak; Riza Aulia (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Sharia monetary policy plays a key role in maintaining price equilibrium and stimulating sustainable economic growth, based on sharia principles. Unlike conventional monetary policy, which relies on interest-based mechanisms, sharia policy emphasizes liquidity management through a profit-sharing system, sharia-compliant money market instruments, and direct linkages with the real business world. Studies have shown that the use of sharia-compliant monetary instruments, including Bank Indonesia Sharia Certificates and sharia-compliant open market transactions, plays a role in controlling inflation and maintaining exchange rate stability. Furthermore, this policy also contributes to economic expansion by increasing productive funding, particularly for the real sector and small and medium-sized enterprises. By avoiding uncertainty and usury, sharia-compliant monetary policy is considered capable of creating a fairer and more resilient economic foundation. However, its effectiveness remains challenged by various constraints, such as limited instruments and low market dominance of sharia banking. Therefore, regulatory strengthening and policy coordination are needed to optimize its impact on the national economy.